社会的敗北ストレスは大脳皮質前頭前野におけるセロトニン再取り込みを減少させる - 田中, 絵理; 田村, 由佳; 矢部, 武士; 永峰, 佑悟; 荒木, 良太 (日本薬理学会年会要旨集, 2020)
Postmortem studies have shown that depressed suicide patients have dysfunctions of serotonergic (5-HTergic) systems in the prefrontal cortex. These 5-HTergic dysfunctions are thought to result from multiple factors including adverse environmental experiences. In this study, to investigate mechanisms by which stressful events cause 5-HTergic dysfunctions, we analyzed function, gene expression and epigenetic modification in 5-HTergic systems in mice exposed to repeated social defeat stress. Extracellular 5-HT levels under basal conditions were increased in the prefrontal cortex of stressed mice. Furthermore, 5-HT uptake and 5-HT transporter expression were decreased in synaptosomes derived from the prefrontal cortex of stressed mice. DNA methylation levels were increased at the CpG island of Slc6a4, a gene encoding 5-HT transporter, in the prefrontal cortex-projecting 5-HTergic neurons of stressed mice. The 5-HT uptake in the prefrontal cortex was correlated with time spent in the open arms in the elevated plus maze test, but not social avoidance or sucrose preference. These findings suggest that stressful events decrease 5-HT reuptake in the prefrontal cortex through decreased expression of 5-HT transporters by DNA methylation at CpG island of Slc6a4.